Depression in Adults with Attention-Deficit/Hyperactivity Disorder (ADHD): The Mediating Role of Cognitive-Behavioral Factors - Knouse, Laura E. (Cognit Ther Res, 2013)
Adults with Attention-Deficit/Hyperactivity Disorder (ADHD) are at increased risk for depressive disorders but little is known about the potential cognitive and behavioral mechanisms of risk that could shape treatment. This study evaluated the degree to which cognitive-behavioral constructs associated with depression and its treatment—dysfunctional attitudes and cognitive-behavioral avoidance—accounted for variance in depressive symptoms and disorder in adults with ADHD. 77 adults clinically diagnosed with ADHD completed self-report questionnaires, diagnostic interviews, and clinician-administered symptom rating scales. Statistical mediation analysis was employed and indirect effects assessed using bootstrap analysis and bias-corrected confidence intervals. Controlling for recent negative life events, dysfunctional attitudes and cognitive-behavioral avoidance fully accounted for the variance between ADHD symptoms and depressive symptoms. Each independent variable partially mediated the other in accounting for depression symptoms suggesting overlapping and unique variance. Cognitive-behavioral avoidance, however, was more strongly related to meeting diagnostic criteria for a depressive disorder than were dysfunctional attitudes. Processes that are targeted in cognitive behavior therapy (CBT) for depression were associated with symptoms in adults with ADHD. Current CBT approaches for ADHD incorporate active coping skills and cognitive restructuring and such approaches could be further tailored to address the ADHD-depression comorbidity.